2014
DOI: 10.5539/ass.v10n4p279
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Workforce Agility and Organizational Intelligence (Case Study: The Companies of "Iran High Council of Informatics")

Abstract: The aim of this study is to explore the relationship between "workforce agility" and "organizational intelligence" (considering the components of both concepts and contextual variables, too).The population included the managers and employees working at the grade one companies of "Iran High Council of Informatics".Results showed a significant positive correlation between workforce agility and organizational intelligence. All components of organizational intelligence (except strategic vision), had a positive sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 16 publications
2
30
1
4
Order By: Relevance
“…These include a positive attitude to the changes, tolerance of uncertain and unexpected, and stressful situations (Sherehiy, 2014). Sohrabi, Asari and Hozoori (2014) and Muduli (2016) were associated with organizational practices, such as employee involvement, organizational structure, organizational intelligence, reward system. One of the essential variables related to workforce agility is organizational learning, which is to create employees to become agile by implementing development or training programs (Alavi et al, 2014;Muduli, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These include a positive attitude to the changes, tolerance of uncertain and unexpected, and stressful situations (Sherehiy, 2014). Sohrabi, Asari and Hozoori (2014) and Muduli (2016) were associated with organizational practices, such as employee involvement, organizational structure, organizational intelligence, reward system. One of the essential variables related to workforce agility is organizational learning, which is to create employees to become agile by implementing development or training programs (Alavi et al, 2014;Muduli, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Employees with higher job positions reflect higher workforce agility. Using the t-test, Sohrabi et al (2014) found a significant difference in the workforce agility score among employees and managers. Similarly, Harvey et al (1999) also found that variables such as work experience and organizational position have a significant positive relationship with workforce agility.…”
Section: 5mentioning
confidence: 98%
“…To date, the literature has touched on many areas of workforce agility, such as identifying internal workforce agility enablers in tax consulting (Thayyib & Khan, 2020); workforce agility index development (Tamtam & Tourabi, 2020); individual, team and enterprise level factors contributing to workforce agility (Petermann & Zacher, 2020); workforce agility enablers in Indian engineering institutions (Menon & Suresh, In press); the relationship between workforce spiritual and psychological empowerment, and workforce agility in the Indian context; (Paul et al, 2020); the psychological antecedents of workforce agility (Storme et al, 2020); measuring workforce agility in IoT projects (Patil & Suresh, 2019); the role of psychological empowerment in workforce agility attributes (Muduli & Pandya, 2018); interlinking psychological empowerment and organizational practices with workforce agility (Muduli, 2016(Muduli, , 2017; organization learning, organization structure (Alavi et al, 2014); the relationship between workforce agility and organizational intelligence (Sohrabi et al, 2014); learning agility and developing "high potential" employees (Dries et al, 2012); employee involvement practices (Sumukadas & Sawhney, 2004); and reviews of the conceptualization of workforce agility (Gunasekaran, 1999).…”
Section: Workforce Agilitymentioning
confidence: 99%
See 2 more Smart Citations